Renal cortex copper concentration in acute copper poisoning in calves - Fazzio, Luis Emilio (2012)
The aim of this study was to estimate the diagnostic value of renal cortex copper (Cu) concentration in clinical cases of acute copper poisoning (ACP). A total of 97 calves that died due to subcutaneous copper administration were compiled in eleven farms. At least, one necropsy was conducted on each farm and samples for complementary analysis were taken. The degree of autolysis in each necropsy was evaluated. The cases appeared on extensive grazing calf breeding and intensive feedlot farms, in calves of 60 to 200 kg body weight. Mortality varied from 0.86 to 6.96 %, on the farms studied. The first succumbed calf was found on the farms between 6 and 72 hours after the susbcutaneous Cu administration. As discrepancies regarding the reference value arose, the local value (19.9 parts per million) was used, confirming the diagnosis of acute copper poisoning in 93% of the analyzed kidney samples. These results confirm the value of analysis of the cortical kidney Cu concentration for the diagnosis of acute copper poisoning.